Analyzing the design of Student Play, an educational module of Agent Socialmetric - Kuz, Antonieta
Currently, the incorporation of Information and Communication Technologies (ICT) into the educational process allows seeing the same from different dimensions. The educational software as an instructional support integrates the contents from a didactic and adapted to the teaching as a fundamental part in the environment of the society of the knowledge and the information. Seeking to deepen the relationship between teachers and students in the courtly context, we have developed a web tool called Agent SocialMetric based on two research areas, social networks and interface conversational agents. Integrating to Agent SocialMetric we extends the tool with a module called Student Play which is responsible for establishing interactive games for students to educate in values, through various interface conversational software agents. In the present research we present the tool and analyzing design considerations that we have taken into account. Finally, we will present the conclusions related to this compilation work.